2021
DOI: 10.1002/jlb.3ma0121-045r
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalisinduces periodontitis, causes immune imbalance, and promotes rheumatoid arthritis

Abstract: Periodontitis induced by bacteria especially Porphyromonas gingivalis (P. gingivalis) is the most prevalent microbial disease worldwide and is a significant risk factor for systemic diseases such as rheumatoid arthritis (RA). RA and periodontitis share similar clinical and pathologic features. Moreover, the prevalence of RA is much higher in patients with periodontitis than in those without periodontitis. To explore the immunologic mechanism of periodontitis involved in RA, we established a mouse model of peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 39 publications
2
30
1
Order By: Relevance
“…The lowest bacterial abundance indicates its contribution as the key stone species [33] and has an important role in periodontitis and the associated systemic conditions [34][35][36]. Moreover, as stated by other reports, P. gingivalis is a keystone pathogen capable of subverting inflammatory and innate responses [37], while F. nucleatum and V. parvula are two crucial species, as they play an important role in shaping oral biofilm ecology [38][39][40]. These two bacteria are positively related to COVID-19associated events [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The lowest bacterial abundance indicates its contribution as the key stone species [33] and has an important role in periodontitis and the associated systemic conditions [34][35][36]. Moreover, as stated by other reports, P. gingivalis is a keystone pathogen capable of subverting inflammatory and innate responses [37], while F. nucleatum and V. parvula are two crucial species, as they play an important role in shaping oral biofilm ecology [38][39][40]. These two bacteria are positively related to COVID-19associated events [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis induced by bacteria especially Gram-negative bacteria is the most prevalent chronic inflammatory disease worldwide [ 15 ]. Infections and the subsequent host immune responses have remodeled an aberrant microenvironment, which generally lead to the dysfunction of PDLSCs, which are the potential “seed cells” for periodontal regeneration applications and bone tissues engineering [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most popular and relevant link appears to be within dysbiosis of the oral microbiome; a recent study found that anti-CCP-positive patients show a dysciotic subgingival microbiome [ 37 ]. In this context, Porphyromonas gingivalis was found to be a key player by causing an immunological imbalance, which promotes RA development and severity [ 38 ]. However, the complexity of RA pathogenesis and, especially, the variety of antirheumatic medications affect the periodontal outcome [ 39 ].…”
Section: Discussionmentioning
confidence: 99%